Toxicity threshold of lead (Pb) to nitrifying microorganisms in soils determined by substrate-induced nitrification assay and prediction model - Han ZHENG; Li CHEN; Ning LI; Bin LIU; Nan MENG; Meng WANG; Shi-bao CHEN (Journal of Integrative Agriculture, 2017)
Abstract: Lead (Pb) contamination has often been recorded in Chinese field soils. In recent years, efforts have been made to investigate Pb toxicity thresholds in soils with plant growth and microbial assays. However, the influence of soil properties on Pb toxicity impacts on soil microbial processes is poorly understood. In this study ten soils with different properties were collected in China to investigate the relationships between thresholds of Pb toxicity to soil microbes and soil properties. The effect of soil leaching on Pb toxicity was also investigated to determine the possible influence of added anions on Pb toxicity during dose-response tests. Toxicity was inferred by measuring substrate-induced nitrification in leached and non-leached soils after Pb addition. We found that soil microbe Pb toxicity thresholds (ECx, x=10, 50) differed significantly between the soils; the 10% inhibition ratio values (EC10) ranged from 86 to 218 mg kg−1 in non-leached soils and from 101 to 313 mg kg−1 in leached soils. The 50% inhibition ratio values (EC50) ranged from 403 to 969 mg kg−1 in non-leached soils and from 494 to 1 603 mg kg−1 in leached soils. Soil leaching increased EC10 and EC50 values by an average leaching factor (LF) of 1.46 and 1.33, respectively. Stepwise multiple regression models predicting Pb toxicity to soil microbes were developed based on ECx and soil properties. Based on these models, soil pH and organic carbon are the most important soil properties affecting Pb toxicity thresholds (R2>0.60). The quantitative relationship between Pb toxicity and soil properties will be helpful for developing soil-specific guidance on Pb toxicity thresholds in Chinese field soils.